Food Standards and Vertical Coordination in Aquaculture: The Case of Pangasius from Vietnam - Neda Trifković (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
This paper explores the interaction between food standards and vertical coordination in the Vietnamese pangasius sector. For farmers and processors alike, the adoption of standards is motivated by a desire to improve market access by ensuring high quality supply. Instead of encouraging the application of standards and contract farming, processing companies prefer to vertically integrate primary production largely due to concerns over the stable supply of pangasius with satisfactory quality and safety attributes. These tendencies increase the market dominance of industrial farming and worsen the position of small household farms.
Keywords: 330; food standards; motivation; vertical coordination; pangasius; Vietnam